Peran Veteran dalam Meningkatkan Nasionalisme dan Semangat Kebangsaan di SD 004 Cisaranten Kulon Kota Bandung - Patmo; Sahidin; Wahyudi; Asep Saipudin (J-Abdimas Cenderawasih, 2025)
Veterans, as witnesses to the nation's history, play a strategic role in instilling patriotic values in the younger generation. This community service program aims to foster students' sense of nationalism and national spirit through the involvement of veteran independence fighters as key speakers. The activity, conducted at SD 004 Cisaranten Kulon, Bandung City, utilized an educational, participatory, and interactive approach on November 20, 2025, with 95 participants. The implementation method included outreach, discussion, and joint reflection activities. The results demonstrated an increase in students' understanding of the nation's struggle, love for their homeland, and motivation to contribute to the nation. This activity also strengthened intergenerational relationships and emphasized the importance of veterans' role as guardians of the national collective memory.